Bullying Impact Analysis On The Social Development Of Students At SDN 2 Dena - Eka Diniarti; Nurwalidainismawati Nurwalidainismawati; Randi Adriansya (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Bullying Causes children to lack motivation, mental health disorders, nightmares, and even death of victims are some of the impacts that often befall children who are victims of violence. However, many teachers still fail to realize that the environment where they teach has the potential to become a place for bullying. This study aims to determine the impact of bullying on students' social and emotional development. The research method uses descriptive qualitative research with a case study approach. The research location was carried out at SDN 2 DENA in Grade 2 located in Dena Village, Madapangga District. Data collection techniques used observation, interviews and documentation. Data validation techniques include format checking, range checking, consistency checking, uniqueness checking, attendance checking, data type checking and reference checking with data processing analysis using the Miles and Huberman stage with 4 stages including data collection, data reduction, data presentation, and conclusion drawing. The results of the study showed that the most dominant impact of bullying occurred in the threat aspect with 24.10%, the verbal aspect 22.56%, the social-emotional aspect 21.02%, and the physical aspect 18.97%, while the relational aspect had the lowest percentage of 1.26%. In conclusion, the bullying activities that occurred at SDN 2 Dena were not only limited to physical violence, but also involved non-physical forms in the form of threats, verbal, and social-emotional, which collectively had a major impact on students. Therefore, it is necessary to implement comprehensive prevention and handling strategies, as well as build a safe and supportive school environment to improve students' social-emotional well-being.